Grid-to-rod flow-induced impact study for PWR fuel in reactor. (August 2016) - Jiang, Hao; Qu, Jun; Lu, Roger Y.; Wang, Jy-An John
Abstract: Dynamic contact impact from hydraulic flow-induced fuel assembly vibration is the source for grid-to-rod fretting in a pressurized water nuclear reactor (PWR). To support grid-to-rod fretting wear mitigation research, finite element analysis (FEA) was used to evaluate the hydraulic flow-induced impact intensity between the fuel rods and the spacer grids. Three-dimensional FEA models, with detailed geometries of the dimple and spring of the actual spacer grids along with fuel rods, were developed for flow impact simulation. The grid-to-rod dynamic impact simulation provided insights of the contact phenomena at grid-rod interface. It is an essential and effective way to evaluate contact forces and provide guidance for simulative bench fretting-impact tests. Highlights: To support grid-to-rod fretting wear research, the flow-induced impact between fuel rods and spacer grids in a pressurized water nuclear reactor (PWR) was studied. 3-D FEA models, with detailed geometries of the dimple and spring of the actual spacer grids along with fuel rods, were developed for flow impact simulation. The grid-to-rod dynamic impact simulation provided insights of the contact phenomena at grid-rod interface. It is an essential and effective way to evaluate contact forces and provide guidance for simulative bench fretting-impact tests.